Regional Disparities in Italy: Developing a Composite Indicator of Physical Activity, Health, and Mobility - Cecchi, Giorgio (REGION, 2026)
Quality of Life in urban settings is intricately tied to active transportation, public health, and physical activity, capturing the growing societal emphasis on sustainable mobility and well-being. This study develops a composite indicator to evaluate regional Quality of Life across Italy, utilizing data from the 2021 ISTAT (Italian National Institute of Statistics) survey “Aspects of Daily Life.” Employing Principal Component Analysis for weighting, the indicator identifies key dimensions of urban well-being, including active transportation, physical activity, and general health. The results reveal pronounced disparities between central-northern and southern Italy, driven by differences in infrastructure, access to health resources, and socio-economic conditions. Northern regions consistently outperform southern counterparts, where structural challenges hinder improvements in Quality of Life. These findings underscore the urgent need for targeted, equity-focused policies to address regional disparities and enhance urban environments, with a particular focus on improving accessibility and public health in underperforming regions. The study provides valuable insights for policymakers aiming to promote sustainable and inclusive urban development.